Teknik Pembakaran Bata Dengan Briket Batu Bara Campuran - Muhammad Halil; Ahmadin Ahmadin; Lelawati Lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2023)
There are many small brick-burning industries in rural areas, and especially near big cities and are industrial centers of bricks burning wood or husks. The price of this fuel continues to increase because the supply of firewood is dwindling and in the use of husks there is competition from other consumers, namely chicken farmers. Coal fuel has a good opportunity to be used in the brick industry, especially in Bengkulu. The coal combustion technique that has been introduced is a combination of coal – 50% wood. In this research, the combustion technique with coal and